Contribution of Guided Discovery Learning Model in Improving Scientific Literacy: Systematic Literature Review - Nadhira Salsabila; Arif Widiyatmoko; Novi Ratna Dewi; Dyah Rini Indriyanti (FKIP - Universitas Riau, 2026)
Scientific literacy needs to be strengthened through science education that engages students in evidence-based inquiry and reasoning. Guided Discovery Learning (GDL) is considered relevant because it guides students in discovering concepts through teacher guidance; however, literature reviews examining the relationship between scientific literacy, science process skills, and critical thinking skills in the context of GDL remain limited. This study aims to analyze the contribution of GDL to these three competencies and to explain the role of science process skills and critical thinking in strengthening scientific literacy. The study employed a Systematic Literature Review following the PRISMA flowchart. Articles were retrieved from Google Scholar, ERIC, and DOAJ between 2021 – 2026 and were then selected based on inclusion criteria. A total of 29 articles met the criteria for qualitative and thematic descriptive analysis. The results of the study indicate that (1) GDL is most frequently reported at the high school level, particularly in Biology, followed by Science, while Chemistry and Physics appear in equal numbers; (2) GDL contributes to scientific literacy by encouraging students to engage in exploration, scientific inquiry, data analysis, and evidence-based conclusion drawing; (3) Science process skills function as procedural abilities in conducting scientific work, while critical thinking plays a role in analyzing information and evaluating evidence.